Zamieszkanie Boga w człowieku jako cel życia duchowego według Anastazego Synaity - Gilski, Marek; Zieliński, Sławomir (Vox Patrum, 2025)
This article aims to answer the question of how Anastasius of Sinai understands God’s dwelling in man. The Sinaitic defines man as the true and rational house of God. The article consists of two parts: the first presents the effects of God’s indwelling in human nature (incarnation), while the second presents the purpose, ways and effects of God’s indwelling in the Christian. Among the most important conclusions are: 1. The indwelling of God in man is the most important goal of life. Correct faith and pious deeds are not enough. A Christian is the one in whom the Holy Trinity has dwelt. 2. The fruit of God’s indwelling in a Christian is worship in Spirit and truth, wisdom, holiness and purity. 3.The effect of God’s indwelling in human nature is the boldness of people toward God as one of them. Angels do not possess this boldness because God did not dwell in their nature. 4. For a man in whom God has taken up residence, external religious practices cease to be important. They only have an auxiliary function in cleansing man from sin.